2014
DOI: 10.1098/rsta.2014.0193
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and their Raman spectroscopic signatures: a spectral challenge for analytical astrobiology

Abstract: The remote robotic exploration of extraterrestrial scenarios for evidence of biological colonization in ‘search for life’ missions using Raman spectroscopy is critically dependent on two major factors: firstly, the Raman spectral recognition of characteristic biochemical spectral signatures in the presence of mineral matrix features; and secondly, the positive unambiguous identification of molecular biomaterials which are indicative of extinct or extant life. Both of these factors are considered here: the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Such pigments are synthesized by a vast range of living organisms, including extremophiles that produce them as part of suites of protectant molecules to aid in the survival of such organisms in hostile environments (Sinha and Häder, 2008). These molecules have been used for some time as biomarkers in terrestrial environments , and it has been suggested that they may also be suitable targets for planetary astrobiology missions (Parnell et al, 2007;McKay et al, 2008;Edwards, 2010;Edwards et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such pigments are synthesized by a vast range of living organisms, including extremophiles that produce them as part of suites of protectant molecules to aid in the survival of such organisms in hostile environments (Sinha and Häder, 2008). These molecules have been used for some time as biomarkers in terrestrial environments , and it has been suggested that they may also be suitable targets for planetary astrobiology missions (Parnell et al, 2007;McKay et al, 2008;Edwards, 2010;Edwards et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For detecting them in the frame of future Mars missions, the application of Raman spectroscopy was proposed [38][39][40]. In fact, it was shown that on the Earth carotenoids can unambiguously be detected in lichen encrustations [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Brownish to black scytonemin is a well‐known UV protective pigment from some cyanobacteria Scytonema , Calothrix , Lynbya. Its distribution was investigated in endolithic microbial communities within the rocks from the Atacama desert, and it is considered as a good biomarker for future exobiological explorations . Other usually dark pigments, such as melanins, play similar protective roles in bacteria, fungi and animals including human.…”
Section: Introductionmentioning
confidence: 99%